Atypical periprosthetic femoral fracture associated with long-term bisphosphonate therapy - Dávid Dózsai; Tamás Ecseri; István Csonka; István Gárgyán; Péter Doró; Ákos Csonka (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Atypical femoral fracture is one of the many complications after the long-term use of bisphosphonates. The American Society for Bone and Mineral Research has officially excluded periprosthetic femoral fractures (PFFs) from the definition of atypical femoral fractures (AFFs). Several case reports found that PFFs can occur with characteristics similar to those of AFFs. The purpose of our study was to evaluate the proportion of atypical fractures among Vancouver type B1 fractures, and to determine the association between the long-term use of bisphosphonates and the occurrence of atypical periprosthetic femoral fractures (APFFs). Methods In this retrospective study, we reviewed 41 patients with Vancouver type B1 periprosthetic fractures between January 1, 2011 and December 31, 2018. We classified them into two groups, namely atypical and typical PFFs, based on the fracture morphology. We noted the proportion of atypical periprosthetic fractures among B1 fractures and identified risk factors. Results Among the 41 PFFs, 5 (13%) fractures were classified as atypical PFF based on the radiological characteristics. The longer duration of bisphosphonate use was probably the only independent risk factor that significantly increases the occurrence of APFF (p = 0.03, 0.08 (CI 0.008 – 0.16)). There were no significant differences in age, gender, body mass index, comorbidities, corticosteroid use, positioning of the femoral stem, the method of fixation (cemented or cementless) and time lapse from before the primary prosthesis implantation to the PFF in the development of atypical fracture type. Conclusions There seems to be a correlation between the long-term intake of bisphosphonates and the atypical periprosthetic fracture. Atypical femoral fracture can also occur in the periprosthetic form. Trial registration Study number: 22/2019-SZTE, http://www.klinikaikutatas.hu/hu/kutatasetika/jovahagyott-vizsgalatok-koezerdeku-adatai/category/25-jovahagyott-vizsgalatok-kozerdeku-adatai-rkeb-2019.html?download=985:22-2019 .